EVALUTION OF THE BEST VACCINAL ROUTES AGAINST NEWCASTLE IN THE PRODUCTION STAGE OF LAYING HENS - Mushtaq T. B. Al-Zuhariy (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
Newcastle disease (ND) is a paramyxovirus-based infectious, highly contagious, and pathogenic avian viral disease. Despite the widespread use of ND vaccinations, ND remains a danger to poultry breeders worldwide. The specific goal of this study was to identify the best vaccination route against ND in the layer hens at production stage following oily vaccine. One hundred chickens at 30 weeks of age were collected from layer flocks (ISSA brown) and randomly divided into four groups. The groups received the following vaccinations: G1: Chicks were vaccinated two doses against ND by (La Sota strain) through drinking water at (30 and 40) weeks. G2: Chicks were vaccinated two doses against ND by (La Sota strain) through cross spray at (30 and 40) weeks. G3: Chicks were vaccinated two doses against ND by (La Sota strain) through intraocular at (30 and 40) weeks. G4: Chicks were not vaccinated and consider as control group. All groups challenge with virulent Newcastle virus isolates in a dose ELD50 105 at 50 weeks. To measure the (IgG, IgA, and IFN-γ) against ND, blood samples were taken at 35, 45, and 55 weeks of age. According to the results of this experiment, the third group, followed by the second group, produced the highest mean (IgG, IgA, and IFN-γ) titres among the vaccinated groups, while the first group produced the lowest titres when compared to the control negative (fourth) group, which recorded the lowest immune response and highly decrease in eggs production. The results were showed that intraocular vaccination with a live vaccine provides layer hens with a higher level of homogenous protection against vvNDV than spraying or drinking water vaccination.